Analisis Strategi Pengembangan Ekonomi Pondok Pesantren Dalailul Khoirot Desa Muntialo Kabupaten Tanjung Jabung Barat - Muhammad Khairul; Ahmad Syukron Prasaja; Eja Armaz Hardi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The role of Islamic boarding schools has created interesting dynamics related to economic, educational, political and social relations. The better the economic status, the quality of education, and the wider the influence of power, the better the culture and traditions that are born and developed through Islamic boarding schools. The aim of this thesis is to determine the management of the economic development strategy of the Dalailul Khoirot Islamic boarding school, Muntialo Village, West Tanjung Jabung Regency. This thesis uses the economic development strategy theory of the Dalailul Khoirot Islamic boarding school, Muntialo Village, West Tanjung Jabung Regency. This thesis uses a qualitative approach, data collection methods through observation, interviews and documentation and analysis methods carried out by data reduction, data presentation and conclusions. The research results show that economic development strategy for the Dalailul Khoirot Islamic boarding school, Muntialo Village, West Tanjung Jabung Regency, is carried out by developing the entrepreneurial spirit of students, practical methods, implementing a partnership pattern, sustainable business units, creating independence and inviting community participation. Constraints in the economic development strategy of the Dalailul Kh Islamic boarding school. Obstacles in the economic development strategy of the Dalailul Khoirot Islamic boarding school, Muntialo Village, West Tanjung Jabung Regency, include low public buying interest and limited facilities and infrastructure. Efforts to develop the economy of the Dalailul Khoirot Islamic boarding school, Muntialo Village, West Tanjung Jabung Regency, include conducting outreach and cooperation and improving facilities and infrastructure.